2012
DOI: 10.1021/op300210j
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration on Pilot-Plant Scale of the Utility of 1,5,7-Triazabicyclo[4.4.0]dec-5-ene (TBD) as a Catalyst in the Efficient Amidation of an Unactivated Methyl Ester

Abstract: The utility of 1,5,7-triazabicyclo[4.4.0]dec-5-ene as a reagent to facilitate efficient amide formation by reaction of an amine with an unactivated ester was demonstrated on pilot-plant scale as a key step in the synthesis of an H-PGDS inhibitor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…HCl, aging for 16 h at 20°C and filtration, 34 kg of the chiral amide was obtained in 88% yield and 99% ee. Weiberth et al 36 have demonstrated direct amidation of an unactivated methyl ester with a benzylamine on pilot-plant scale using 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD) as the catalyst. 37 The optimum reaction, identified after a DoE study, employed a slight excess of the ester (1.06 equiv.…”
Section: General Methods For Catalytic/sustainable (Direct) Amide or mentioning
confidence: 99%
“…HCl, aging for 16 h at 20°C and filtration, 34 kg of the chiral amide was obtained in 88% yield and 99% ee. Weiberth et al 36 have demonstrated direct amidation of an unactivated methyl ester with a benzylamine on pilot-plant scale using 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD) as the catalyst. 37 The optimum reaction, identified after a DoE study, employed a slight excess of the ester (1.06 equiv.…”
Section: General Methods For Catalytic/sustainable (Direct) Amide or mentioning
confidence: 99%
“…And cyclic ester and a-electron-withdrawing group substituted esters reacted well with aromatic and aliphatic amines (Table 3, 11a, 11b, 12a, 13a). Moreover, in the cases of diesters the selective amidation was achieved via the controllable conditions (Table 3, [14][15][16]. Unfortunately, amidation of diethyl oxalate produced monoamidated product as only main product even after a prolonged reaction time of 60 min at 140°C (Table 3, 14a-14b) while phthalimide was observed by using phthalic acid ester (Table 3, 22a).…”
Section: Introductionmentioning
confidence: 99%
“…14,15 In recent years, catalytic approaches enabling the aminolysis of esters have been reported, however drawbacks such as limited scope of the acylating species and the use of finite and toxic transition or rare earth metals have hindered their application. [16][17][18][19][20][21][22] The use of multicomponent reactions (MCRs) is an attractive approach to synthesize complex and structurally diverse products rapidly from simple starting materials, with most, if not all, of the atoms retained in the final product. 23 When applied to amide bond formation, multicomponent reactions would offer an efficient and atom economical approach, mitigating the requirement for stoichiometric coupling reagents, and hence the formation of associated by-products.…”
mentioning
confidence: 99%